Rift Valley fever (RVF) project on Zooniverse, a citizen science platform that allows registered volunteers to identify animals in landscapes from drone imagery - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
A4NH researchers from the London School of Hygiene and Tropical Medicine set up this project page on Zooniverse, pending beta review and a public launch. In addition to its role in developing transmission models, the data could be used for developing machine learning algorithms to automatically identity animals in landscapes.